A Comparison of Professional Value Development Among Pre-Licensure Nursing Students in Associate Degree, Diploma, and Bachelor of Science in Nursing Programs. - Fisher, MaryDee (Nursing Education Perspectives (National League for Nursing), 2014)
AIM The aim of the study was to compare the development of professionalism in pre-licensure nursing students in associate degree, diploma, and baccalaureate programs. BACKGROUND Concerns have been raised about whether professional values to guide nursing practice are consistently instilled within nursing education programs. METHOD Degrees of professionalism were operationally measured by the 26-item Nurses Professional Values Scale-Revised (NPVS-R) (Weis & Schank, 2009) in a convenience sample. RESULTS ANOVA analysis (p = 0.0003) and then pairwise t-test analysis (p = 0.0004) revealed statistical significance when comparing NPVS-R scores and educational preparation. Differences between professional values scores and levels within each program revealed significance for the diploma students (p < 0.0001). Secondary subanalysis of the NPVS-R factors among levels and between educational preparation again revealed significance. CONCLUSION Curricula revisions, faculty reflection and enrichment, as well as active student engagement are warranted to more vigilantly enhance the role formation process.